First Clinical Experiences with Microfocused Ultrasound in Infraorbital Rejuvenation: A Clinically and Scientifically Grounded Perspective - Heitzmann, Wolfram; Schiefer, Jennifer Lynn; Lanckohr, Laura; Visnovska, Diana; Schulz, Alexandra (Facial Plastic Surgery, 2025)
The infraorbital region is challenging to treat due to complex anatomy and issues like skin laxity, malar edema, and malar mounds. This study evaluates micro focused ultrasound with visualization (MFU-V) as a non-invasive treatment for infraorbital rejuvenation, hypothesizing improved skin tightening and contouring.A case series with anatomical analysis and literature review.Five female patients (aged 42–54) with mild-to-moderate skin laxity underwent MFU-V treatment using 1.5, 3.0, and 4.5 mm transducers. Standardized photos and assessment scales (Merz Infraorbital Hollow Scale, GAIS) were used at baseline and 6 months.MFU-V led to visible improvements in periorbital skin tightening and reduction of malar mounds, especially in more pronounced cases. No adverse effects occurred.MFU-V is a safe, effective, and non-invasive option for periorbital rejuvenation. It may serve as an alternative to surgical treatment for infraorbital skin laxity and malar deformities. Larger studies are needed to confirm efficacy.
Keywords: malar mounds; facial rejuvenation; microfocused ultrasound